Predictors of hospitalization for acute lower respiratory infections during the first two years of life in a population of preterm infants with bronchopulmonary dysplasia (2020)
Background: There have been few research studies aimed at obtaining a better understanding of the prediction of subsequent respiratory morbidity at follow-up in infants with a previous history of bronchopulmonary dysplasia (BPD) living in low- and middle-income countries (LMIC). The aim of the present study was to identify predictors of hospitalization for acute lower respiratory infections (ALRIs) in a population of infants with a history of BPD living in a LMIC. Methods: In a prospective cohort study, we determined independent predictors of the number of hospitalizations for ALRIs during the first two years of life in a population of infants with a history of BPD living in Bogota, Colombia. In multivariate analyses, we included both clinico-demographic variables and underlying disease characteristics as predictor variables of hospitalization for ALRIs. Results: Of a total of 138 patients included in the study, 83 (60.1%) had at least one hospitalization for ALRI during the follow-up period. Independent predictors of the number of hospitalizations for ALRIs included duration of neonatal ventilatory support (IRR 1.02; CI 95% 1.00–1.03; p = 0.010), duration of subsequent ambulatory oxygen therapy (IRR 2.06; CI 95% 1.16–3.64; p = 0.013), and breastfeeding in females (IRR 0.35; CI 95% 0.14–0.84; p = 0.019). Conclusions: Duration of mechanical ventilation, duration of subsequent ambulatory oxygen therapy, and breastfeeding in females were independently associated with the number of hospitalizations for ALRIs in our population of infants with a history of BPD.